Analisa Pengaruh Motivasi, Inisiatif, Kompensasi, Pendidikan Dan Pelatihan Terhadap Rendahnya Kinerja Tenaga Pemasar PT Bank Brisyariah Tbk Kantor Cabang Surabaya Diponegoro - Maya, Eryca Putri Wahyu Listia (Fakultas Ekonomi Universitas Wisnuwardhana, 2019)
Abstract: The intense competition in the banking industry inIndonesia is currently marked by the development of a largenumber of state-owned and private banks, conventional andsharia, demanding that PT Bank BRISyariah Tbk be able tocompete with other banks in order to survive anddevelop.Banking in general has made improvements in morediverse product and service innovations for consumers. Inthis case the support of marketers is very importantconsidering that marketers are the frontline service in thebanking industry and are also the spearhead of thecompany's success in achieving targeted marketshare.However, for the improvement efforts made by PTBank BRISyariah Tbk, the Diponegoro Surabaya BranchOffice (KC) is inversely proportional to the achievement ofthe PT Bank BRISyariah Tbk financing target of theDiponegoro Surabaya Branch Office (KC) which showedunsatisfactory results. The percentage of achievement of thefinancing target is far from what is stipulated in the BankBusiness Plan every year. The decrease in the percentage ofthis target was accompanied by a decline in customer growthin terms of the amount and volume of financing.This studyuses a quantitative approach, and uses causal analysis whichaims to determine the magnitude of the effect or effect ofindependent variables on changes that occur in thedependent variable. Data collection methods used throughpreliminary surveys, questionnaires and literature. Thepopulation in this study were all marketers who numbered 38from 1 Diponegoro Branch Office (KC) and 6 Sub-BranchOffices. And the population for the performance variable isthe direct leader of each marketer, which consists of 2branch managers and 6 branch managers. The results of thisArthavidya Jurnal Ilmiah Ekonomi Oktober 2019 | 151study indicate that there is a positive and significantinfluence between motivation on performance; initiative onperformance; compensation for performance; education &training on performance.Keywords: performance, performance appraisal, measuringperformance, performance management, motivation,initiative, compensation, education and training